Synthesis and Optimization of MWCNTs on Co-Ni/MgO by Thermal CVD - H. Ryu; B. K. Singh; K. S. Bartwal (Advances in Condensed Matter Physics)
Multiwalled carbon nanotubes (MWCNTs) were prepared by the thermal chemical vapor deposition (CVD) technique. Monometallic and bimetallic Co and Ni combinations were used as a catalyst on MgO support. The mixer of H2/C2H2 was used as a carbon source. The prepared CNTs were found to possess different shapes, morphologies, and sizes. Maximum yield was found for 50% Co (MgO: 50% and Ni: 0%) catalyst at 600°C. Scanning electron microscopy (SEM) and high-resolution transmission electron microscopy (HRTEM) techniques were used for structural analysis. Raman spectra were taken to investigate the quality and crystalline perfection of the prepared CNTs. The ratio of D- and G-bands (ID/IG) was measured from these spectra.